Urgência odontológica na primeira infância: perfil do atendimento das Unidades de Saúde de Urgência da Secretaria Municipal de Saúde de Goiânia - Machado, Geovanna de Castro Morais (2013)
Aim: The aim of this study was to describe how the community centers from the the city of Goiania handled dental emergency care in children under 6 years during 2011. Methods: This quantitative study evaluated the dental charts of children under 6 years old of age focusing on emergent dental care and assessed dental emergency risk classification, child’s age and gender, chief complaint, involved teeth, clinical procedures performed, medications prescribed and referral. Data were recorded on forms for later descriptive analysis. Results: 1,108 children under 6 years old (4.0%) were treated, 556 male (50.2%), with a mean age of 3.7 years old (±1.4). The most reported chief complaints were toothache (47.9%, n=531) and dental trauma (20.0%, n=221). The most frequently performed clinical procedures were extraction (13.0%) and endodontic treatment (13.0%). No clinical procedures were performed in 58.5% of the cases (n=649). Conclusion: Emergency dental care for children under 6 years occurs mainly as a result of dental decay. It is necessary that emergency dental public services have a more effective management of these situations.